Association of cardiovascular risk burden with cognitive trajectories and structural brain differences: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Song, Ruixue; Xu, Hui; Dintica, Christina S.; Pan, Kuan‐Yu; Qi, Xiuying; Buchman, Aron S; Bennett, David A; Xu, Weili
Abstract: Background: The impact of cardiovascular risk burden on cognitive trajectories and brain structure changes remains unclear. Method: Within the Rush Memory and Aging Project, 1, 588 dementia‐free participants (mean age=79.5 years) were followed for up to 21 years. FGCRS was assessed at baseline and categorized into tertiles (the lowest, middle, and the highest). Episodic memory, semantic memory, working memory, visuospatial ability, and perceptual speed were assessed annually with a battery of 19 tests, from which composite scores were derived. A subsample (n=378) of the participants underwent magnetic resonance imaging (MRI). Structural total and regional brain volumes were estimated. Data were analyzed using linear mixed‐effects models and linear regression models. Result: In all participants, FGCRS ranged from 4 to 28 (mean score=15.6±3.7). Compared with the lowest tertile of FGCRS, the highest was associated with faster decline in global cognition (β=‐0.019, 95% confidence interval [CI] ‐0.035 to ‐0.003), episodic memory (β=‐0.023, 95% CI ‐0.041 to ‐0.004), working memory (β=‐0.021, 95% CI ‐0.035 to ‐0.007), and perceptual speed (β=‐0.027, 95% CI ‐0.042 to ‐0.011) over the follow‐up. In MRI data analyses, higher FGCRS was related to smaller volumes of the hippocampus (β=‐0.021, 95% CI ‐0.042 to ‐0.000), total gray matter (β=‐1.569 95% CI ‐2.757 to ‐0.382), and total brain (β=‐1.588, 95% CI ‐2.832 to ‐0.344), and greater volume of white matter hyperintensities (β=0.035, 95% CI 0.001 to 0.069). Conclusion: Higher cardiovascular risk burden may predict decline in episodic memory, working memory and perceptual speed, and is associated with neurodegeneration and vascular lesions in the brain.